3D-printed β-TCP/S53P4 bioactive glass scaffolds coated with tea tree oil: Coating optimization, in vitro bioactivity and antibacterial properties - Alves, Ana Paula Nogueira; Arango Ospina, Marcela; Oliveira, Rodrigo Luiz Moraes Saldanha; Ferreira, Igor Maia; de Moraes, Elisângela Guzi; Hartmann, Malte; de Oliveira, Antônio Pedro Novaes; Boccaccini, Aldo R.; de Sousa Trichês, Eliandra (Journal of Biomedical Materials Research Part B: Applied Biomaterials, 2022)
Bone infection treatment is a significant challenge for the orthopedic field. 3D printing is a promising technology to produce scaffolds with customized architecture, able to stimulate and support bone growth. β-TCP and S53P4 bioactive glass (BG) are well-known biomaterials for scaffold manufacturing. However, a multifunctional scaffold, able to inhibit microbial proliferation at the defect site, is of increasing interest to avoid infection recurrence. Tea tree oil (TTO) has aroused interest as an antimicrobial agent to minimize the use of antibiotics. Therefore, combining the regenerative potential of a bioceramic with TTO's antimicrobial properties could result in a scaffold capable of stimulating tissue growth and treating infections. In this context, this study aimed to produce and characterize 3D-printed β-TCP/S53P4 BG scaffolds coated with TTO. Scaffolds morphological and chemical characterizations were carried out through XDR, SEM, and FTIR analysis. β-TCP/S53P4 BG scaffolds showed a compressive strength of 2 MPa and 53 ± 2% of porosity. The scaffolds were coated by two different procedures, using an ethanol/TTO (EtOH/TTO) and a gelatin/TTO (Gel/TTO) solution with 5, 10, and 15% (v/v) TTO. The addition of TTO decreased MG-63 cell viability for both coating groups, but the Gel/TTO group showed higher cell viability. The antibacterial activity of the coated scaffolds was evaluated against S. aureus and higher inhibition of colony formation was found for Gel/TTO group. Therefore, the coating with Gel/TTO was effective in terms of antibacterial activity and cell viability. Such Gel/TTO coated β-TCP/S53P4 BG scaffolds are proposed for antibacterial bone tissue engineering.
CRIS-Team Scopus Importer:2022-12-16
Keywords: 3D printing; antibacterial activity; S53P4 bioactive glass; scaffolds; tea tree oil; β-Tricalcium phosphate

A comparative analysis of the cytocompatibility, protein adsorption, osteogenic and angiogenic properties of the 45S5- and S53P4-bioactive glass compositions - Westhauser, Fabian; Arango Ospina, Marcela; Hupa, Leena; Renkawitz, Tobias; Boccaccini, Aldo R.; Kunisch, Elke (Biomedical Materials, 2024)
Despite their long history of application in orthopedics, the osteogenic and angiogenic properties as well as the cytocompatibility and protein adsorption of the 45S5- (in wt%: 45.0 SiO2, 24.5 Na2O, 24.5 CaO, 6.0 P2O5) and S53P4- (in wt%: 53.0 SiO2, 23.0 Na2O, 20.0 CaO, 4.0 P2O5) bioactive glass (BG) compositions have not yet been directly compared in one and the same experimental setting. In this study, the influence of morphologically equal granules of both BGs on proliferation, viability, osteogenic differentiation and angiogenic response of human bone-marrow-derived mesenchymal stromal cells (BMSCs) was assessed. Furthermore, their impact on vascular tube formation and adsorption of relevant proteins was evaluated. Both BGs showed excellent cytocompatibility and stimulated osteogenic differentiation of BMSCs. The 45S5-BG showed enhanced stimulation of bone morphogenic protein 2 (BMP2) gene expression and protein production compared to S53P4-BG. While gene expression and protein production of vascular endothelial growth factor (VEGF) were stimulated, both BGs had only limited influence on tubular network formation. 45S5-BG adsorbed a higher portion of proteins, namely BMP2 and VEGF, on its surface. In conclusion, both BGs show favorable properties with slight advantages for 45S5-BG. Since protein adsorption on BG surfaces is important for their biological performance, the composition of the proteome formed by osteogenic cells cultured on BGs should be analyzed in order to gain a deeper understanding of the mechanisms that are responsible for BG-mediated stimulation of osteogenic differentiation.
CRIS-Team Scopus Importer:2024-02-23
Keywords: 45S5-bioactive glass; angiogenesis; bioactive glass; cytocompatibility; osteogenesis; protein adsorption; S53P4-bioactive glass

A comparative in vitro and in vivo analysis of the biological properties of the 45S5-, 1393-, and 0106-B1-bioactive glass compositions using human bone marrow-derived stromal cells and a rodent critical size femoral defect model - Kunisch, Elke; Fiehn, Linn Anna; Saur, Merve; Arango Ospina, Marcela; Merle, Christian; Hagmann, Sébastien; Stiller, Adrian; Hupa, Leena; Renkawitz, Tobias; Boccaccini, Aldo R.; Westhauser, Fabian (Biomaterials Advances, 2023)
Since the introduction of the 45S5-bioactive glass (BG), numerous new BG compositions have been developed. Compared to the 45S5-BG, 1393-BG shows favorable processing properties due to its low crystallization tendency and the 1393-BG-based borosilicate 0106-B1-BG exhibits improved angiogenic properties due to its boron content. Despite their close (chemical) relationship, the biological properties of the mentioned BG composition have not yet been comparatively examined. In this study, the effects of the BGs on proliferation, viability, osteogenic differentiation, and angiogenic factor production of human bone marrow-derived mesenchymal stromal cells were assessed. Scaffolds made of the BGs were introduced in a critical-sized femur defect model in rats in order to analyze their impact on bone defect regeneration. In vitro, 1393-BG and 0106-B1-BG outperformed 45S5-BG with regard to cell proliferation and viability. 1393-BG enhanced osteogenic differentiation; 0106-B1-BG promoted angiogenic factor production. In vivo, 0106-B1-BG and 45S5-BG outperformed 1393-BG in terms of angiogenic and osteoclastic response resulting in improved bone regeneration. In conclusion, the biological properties of BGs can be significantly modified by tuning their composition. Demonstrating favorable processing properties and an equally strong in vivo bone regeneration potential as 45S5-BG, 0106-B1-BG qualifies as a basis to incorporate other bioactive ions to improve its biological properties.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Angiogenesis; Bioactive glass; Biomaterials; Bone defect regeneration; Mesenchymal stromal cells; Osteogenesis

A comparative in vitro and in vivo analysis of the impact of copper substitution on the cytocompatibility, osteogenic, and angiogenic properties of a borosilicate bioactive glass - Fiehn, Linn Anna; Kunisch, Elke; Saur, Merve; Arango Ospina, Marcela; Merle, Christian; Hagmann, Sébastien; Stiller, Adrian; Hupa, Leena; Kaňková, Hana; Galusková, Dagmar; Renkawitz, Tobias; Boccaccini, Aldo R.; et al. (Journal of Biomedical Materials Research Part A, 2024)
The 0106-B1-bioactive glass (BG) composition (in wt %: 37.5 SiO2, 22.6 CaO, 5.9 Na2O, 4.0 P2O5, 12.0 K2O, 5.5 MgO, and 12.5 B2O3) has demonstrated favorable processing properties and promising bone regeneration potential. The present study aimed to evaluate the biological effects of the incorporation of highly pro-angiogenic copper (Cu) in 0106-B1-BG in vitro using human bone marrow-derived mesenchymal stromal cells (BMSCs) as well as its in vivo potential for bone regeneration. CuO was added to 0106-B1-BG in exchange for CaO, resulting in Cu-doped BG compositions containing 1.0, 2.5 and 5.0 wt % CuO (composition in wt %: 37.5 SiO2, 21.6/ 20.1/17.6 CaO, 5.9 Na2O, 4.0 P2O5, 12.0 K2O, 5.5 MgO, 12.5 B2O3, and 1.0/ 2.5/ 5.0 CuO). In vitro, the BGs' impact on the viability, proliferation, and growth patterns of BMSCs was evaluated. Analyses of protein secretion, matrix formation, and gene expression were used for the assessment of the BGs' influence on BMSCs regarding osteogenic differentiation and angiogenic stimulation. The presence of Cu improved cytocompatibility, osteogenic differentiation, and angiogenic response when compared with unmodified 0106-B1-BG in vitro. In vivo, a critical-size femoral defect in rats was filled with scaffolds made from BGs. Bone regeneration was evaluated by micro-computed tomography. Histological analysis was performed to assess bone maturation and angiogenesis. In vivo effects regarding defect closure, presence of osteoclastic cells or vascular structures in the defect were not significantly changed by the addition of Cu compared with undoped 0106-B1-BG scaffolds. Hence, while the in vitro properties of the 0106-B1-BG were significantly improved by the incorporation of Cu, further evaluation of the BG composition is necessary to transfer these effects to an in vivo setting.
CRIS-Team Scopus Importer:2024-05-03
Keywords: angiogenesis; bioactive glass; bone defect regeneration; boron; copper; mesenchymal stromal cells; osteogenesis

An in vitro evaluation of the biological and osteogenic properties of magnesium-doped bioactive glasses for application in bone tissue engineering - Hohenbild, Frederike; Arango Ospina, Marcela; Schmitz, Sarah I.; Moghaddam, Arash; Boccaccini, Aldo R.; Westhauser, Fabian (International Journal of Molecular Sciences, 2021)
Magnesium (Mg2+ ) is known to play a crucial role in mineral and matrix metabolism of bone tissue and is thus increasingly considered in the field of bone tissue engineering. Bioactive glasses (BGs) offer the promising possibility of the incorporation and local delivery of therapeutically active ions as Mg2+ . In this study, two Mg2+-doped derivatives of the ICIE16-BG composition (49.46 SiO2, 36.27 CaO, 6.6 Na2 O, 1.07 P2 O5, 6.6 K2 O (mol%)), namely 6Mg-BG (49.46 SiO2, 30.27 CaO, 6.6 Na2 O, 1.07 P2 O5, 6.6 K2 O, 6.0 MgO (mol%) and 3Mg-BG (49.46 SiO2, 33.27 CaO, 6.6 Na2 O, 1.07 P2 O5, 6.6 K2 O, 3.0 MgO (mol%)) were examined. Their influence on viability, proliferation and osteogenic differentiation of human mesenchymal stromal cells (MSCs) was explored in comparison to the original ICIE16-BG. All BGs showed good biocompatibility. The Mg2+-doped BGs had a positive influence on MSC viability alongside with inhibiting effects on MSC proliferation. A strong induction of osteogenic differentiation markers was observed, with the Mg2+-doped BGs significantly outperforming the ICIE16-BG regarding the expression of genes encoding for protein members of the osseous extracellular matrix (ECM) at certain observation time points. However, an overall Mg2+-induced enhancement of the expression of genes encoding for ECM proteins could not be observed, possibly due to a too moderate Mg2+ release. By adaption of the Mg2+ release from BGs, an even stronger impact on the expression of genes encoding for ECM proteins might be achieved. Furthermore, other BG-types such as mesoporous BGs might provide a higher local presence of the therapeutically active ions and should therefore be considered for upcoming studies.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Human mesenchymal stromal cell; ICIE16 bioactive glass; Magnesium; Osteogenic differentiation; Therapeutically active ions

Apatite forming ability and dissolution behavior of boron- And calcium-modified silicon oxycarbides in comparison to silicate bioactive glass - Xie, Fangtong; Gonzalo Juan, Isabel; Arango Ospina, Marcela; Riedel, Ralf; Boccaccini, Aldo R.; Ionescu, Emanuel (ACS Biomaterials Science and Engineering, 2019)
The bioactivity of Ca and/or B modified silicon oxycarbides has been assessed in vitro upon immersion in SBF (simulated body fluid). In the context of the present work, bioactivity refers to the likeliness of hydroxyapatite crystallization (biomineralization) on the surface of a material when in contact with physiological fluids. The incorporation of Ca and B into the silicon oxycarbide glass network is found to increase its bioactivity, which seems to scale with the content of Ca; thus, SiOC glass with a relatively large Ca/Si molar ratio (i.e., 0.12) is shown to exhibit bioactive characteristics similar to those of the benchmark silicate bioactive glass of 45S5 composition. The release kinetics of the SiOC glasses modified with Ca and/or B during the SBF test was studied by inductively coupled plasma-optical emission spectroscopy. It has been observed that the Si release kinetics can be correlated with the Ca content in the SiOC glasses: SiOC based glasses modified with Ca exhibited low Si release activation energies (i.e., 0.07 eV), being comparable to that of 45S5 bioactive glass (i.e., 0.04 eV); whereas silicon oxycarbides without Ca modification showed higher activation energies for Si release (i.e., 0.27 eV).
CRIS-Team Scopus Importer:2019-10-18
Keywords: bioactive glass; bioactivity; network connectivity; silicon oxycarbide

Bioactive glass (Bg) icie16 shows promising osteogenic properties compared to crystallized 45s5-bg - Westhauser, Fabian; Hohenbild, Frederike; Arango Ospina, Marcela; Schmitz, Sarah I.; Wilkesmann, Sebastian; Hupa, Leena; Moghaddam, Arash; Boccaccini, Aldo R. (International Journal of Molecular Sciences, 2020)
The ICIE16-bioactive glass (BG) (48.0 SiO2, 6.6 Na2O, 32.9 CaO, 2.5 P2O5, 10.0 K2O (wt %)) has been developed as an alternative to 45S5-BG, the original BG composition (45.0 SiO2, 24.5 Na2O, 24.5 CaO, 6.0 P2O5 (wt %)), with the intention of broadening the BG sintering window while maintaining bioactivity. Because there is a lack of reports on ICIE16-BG biological properties, the influence of ICIE16-BG on viability, proliferation, and osteogenic differentiation of human mesenchymal stromal cells (MSCs) was evaluated in direct comparison to 45S5-BG in this study. The BGs underwent heat treatment similar to that which is required in order to fabricate scaffolds by sintering, which resulted in crystallization of 45S5-BG (45S5-CBG) while ICIE16 remained amorphous. Granules based on both BGs were biocompatible, but ICIE16-BG was less harmful to cell viability, most likely due to a more pronounced pH alkalization in the 45S5-CBG group. ICIE16- BG outperformed 45S5-CBG in terms of osteogenic differentiation at the cellular level, as determined by the increased activity of alkaline phosphatase. However, granules from both BGs were comparable regarding the stimulation of expression levels of genes encoding for osseous extracellular matrix (ECM) proteins. The addition of therapeutically active ions to ICIE16-BG might further improve its ability to stimulate ECM production and should be investigated in upcoming studies.
CRIS-Team Scopus Importer:2020-03-10
Keywords: 45S5 bioactive glass; Human mesenchymal stromal cells; ICIE16 bioactive glass; Osteogenic differentiation; Proliferation

Bioactive glasses incorporating less-common ions to improve biological and physical properties - Pantulap, Usanee; Arango Ospina, Marcela; Boccaccini, Aldo R. (Journal of Materials Science: Materials in Medicine, 2022)
Bioactive glasses (BGs) have been a focus of research for over five decades for several biomedical applications. Although their use in bone substitution and bone tissue regeneration has gained important attention, recent developments have also seen the expansion of BG applications to the field of soft tissue engineering. Hard and soft tissue repair therapies can benefit from the biological activity of metallic ions released from BGs. These metallic ions are incorporated in the BG network not only for their biological therapeutic effects but also in many cases for influencing the structure and processability of the glass and to impart extra functional properties. The "classical" elements in silicate BG compositions are silicon (Si), phosphorous (P), calcium (Ca), sodium (Na), and potassium (K). In addition, other well-recognized biologically active ions have been incorporated in BGs to provide osteogenic, angiogenic, anti-inflammatory, and antibacterial effects such as zinc (Zn), magnesium (Mg), silver (Ag), strontium (Sr), gallium (Ga), fluorine (F), iron (Fe), cobalt (Co), boron (B), lithium (Li), titanium (Ti), and copper (Cu). More recently, rare earth and other elements considered less common or, some of them, even "exotic" for biomedical applications, have found room as doping elements in BGs to enhance their biological and physical properties. For example, barium (Ba), bismuth (Bi), chlorine (Cl), chromium (Cr), dysprosium (Dy), europium (Eu), gadolinium (Gd), ytterbium (Yb), thulium (Tm), germanium (Ge), gold (Au), holmium (Ho), iodine (I), lanthanum (La), manganese (Mn), molybdenum (Mo), nickel (Ni), niobium (Nb), nitrogen (N), palladium (Pd), rubidium (Rb), samarium (Sm), selenium (Se), tantalum (Ta), tellurium (Te), terbium (Tb), erbium (Er), tin (Sn), tungsten (W), vanadium (V), yttrium (Y) as well as zirconium (Zr) have been included in BGs. These ions have been found to be particularly interesting for enhancing the biological performance of doped BGs in novel compositions for tissue repair (both hard and soft tissue) and for providing, in some cases, extra functionalities to the BG, for example fluorescence, luminescence, radiation shielding, anti-inflammatory, and antibacterial properties. This review summarizes the influence of incorporating such less-common elements in BGs with focus on tissue engineering applications, usually exploiting the bioactivity of the BG in combination with other functional properties imparted by the presence of the added elements.
CRIS-Team WoS Importer:2021-12-31

Bioactive glass selectively promotes cytotoxicity towards giant cell tumor of bone derived neoplastic stromal cells and induces MAPK signalling dependent autophagy - Fellenberg, Joerg; Losch, Sarina; Lehner, Burkhard; Arango Ospina, Marcela; Boccaccini, Aldo R.; Westhauser, Fabian (Bioactive Materials, 2022)
Giant cell tumors of bone (GCTB) are associated with massive bone destructions and high recurrence rates. In a previous study, we observed cytotoxic effects of three different compositions of bioactive glasses (BGs) towards GCTSC but not bone marrow derived stromal cells (BMSC) indicating that BGs represent promising candidates for the development of new therapeutic approaches. In the current study we aimed to investigate the molecular mechanisms that are involved in BG induced cytotoxicity. We observed, that BG treatment was not associated with any signs of apoptosis, but rather led to a strong induction of mitogen activated protein kinases (MAPK) and, as a consequence, upregulation of several transcription factors specifically in GCTSC. Genome wide gene expression profiling further revealed a set of fifteen genes that were exclusively induced in GCTSC or induced significantly stronger in GCTSC compared to BMSC. BG treatment further induced autophagy that was significantly more pronounced in GCTSC compared to BMSC and could be inhibited by MAPK inhibitors. Together with the known osteogenic properties of BGs our findings support the suitability of BGs as therapeutic agents for the treatment of GCTB. However, these data have to be verified under in vivo conditions.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Autophagy; Bioactive glass; Cytotoxicity; Giant cell tumor of bone; Mesenchymal stromal cells; Mitogen-activated protein kinases

Bioactivity and dissolution behavior of boron-containing bioactive glasses under static and dynamic conditions in different media - Arango Ospina, Marcela; Hupa, Leena; Boccaccini, Aldo R. (Biomedical Glasses, 2019)
Keywords: silicate glasses; Bioactive glasses; boron; bioactivity; lactic acid; dynamic dissolution

Biological effects of a zinc-substituted borosilicate bioactive glass on human bone marrow derived stromal cells in vitro and in a critical-size femoral defect model in rats in vivo - Saur, M.; Kunisch, E.; Fiehn, L. A.; Arango Ospina, Marcela; Merle, C.; Hagmann, S.; Moghaddam, A.; Stiller, A.; Hupa, L.; Renkawitz, T.; Kaňková, H.; Galusková, D.; et al. (Biomaterials Science, 2024)
The borosilicate 0106-B1-bioactive glass (BG) composition (in wt%: 37.5 SiO2, 22.6 CaO, 5.9 Na2O, 4.0P2O5, 12.0 K2O, 5.5 MgO, 12.5 B2O3) has shown favorable processing characteristics and bone regeneration ability. This study investigated the addition of zinc (Zn) to 0106-B1-BG as an approach to improve this BG's biological properties. Different proportions of ZnO were substituted for CaO in 0106-B1-BG, resulting in three new BG-compositions: 1-Zn-BG, 2-Zn-BG, 3-Zn-BG (in wt%: 37.5 SiO2, 21.6/20.1/17.6 CaO, 4.0 P2O5, 5.9 Na2O, 12.0 K2O, 5.5 MgO, 12.5 B2O3 and 1.0/2.5/5.0 ZnO). Effects of the BG compositions on cytocompatibility, osteogenic differentiation, extracellular matrix deposition, and angiogenic response of human bone marrow-derived mesenchymal stromal cells (BMSCs) were evaluated in vitro. Angiogenic effects were assessed using a tube formation assay containing human umbilical vein endothelial cells. The in vivo osteogenic and angiogenic potentials of 3-Zn-BG were investigated in comparison to the Zn-free 0106-B1-BG in a rodent critical-size femoral defect model. The osteogenic differentiation of BMSCs improved in the presence of Zn. 3-Zn-BG showed enhanced angiogenic potential, as confirmed by the tube formation assay. While Zn-doped BGs showed clearly superior biological properties in vitro, 3-Zn-BG and 0106-B1-BG equally promoted the formation of new bone in vivo; however, 3-Zn-BG reduced osteoclastic cells and vascular structures in vivo. The acquired data suggests that the differences regarding the in vivo and in vitro results may be due to modulation of inflammatory responses by Zn, as described in the literature. The inflammatory effect should be investigated further to promote clinical applications of Zn-doped BGs.
CRIS-Team Scopus Importer:2024-08-23

Effect of glycerol and H3PO4 on the bioactivity and degradability of rod-like SBA-15 particles with active surface for bone tissue engineering applications - Vargas-Osorio, Zulema; Klotschan, Artem; Arango Ospina, Marcela; Piñeiro, Yolanda; Liverani, Liliana; Rivas, José; Michálek, Martin; Galusek, Dušan; Boccaccini, Aldo R. (Microporous and Mesoporous Materials, 2022)
In the quest to increase the quality of life and life expectancy, there is a great demand to develop advanced medical devices capable of facing current health challenges. Santa Barbara Amorphous (SBA-15) mesoporous silica has been demonstrated to be a remarkable option for a variety of biomedical applications, from tissue engineering to drug delivery, due to its unique hierarchical porous structure. This work reports on the effect of using different ratios and concentrations of an acid mixture mediated by HCl/H3PO4 that in combination with a glycerol-modified silane precursor favoured obtaining bioactive SBA-15 mesoporous silica rods. The surfactant was removed by solvent extraction which allowed to keep a substantial amount of silanol groups (SiOH) at the surface. All the evaluated samples showed homogeneous rod shape and particle size, as well as high bioactivity after being immersed for 14 days in simulated body fluid (SBF). Different structural arrangements of needle-type carbonate hydroxyapatite (HCA) crystals were produced from SBA-15 upon immersion in SBF. By scanning electron microscopy (SEM) characterization, it was observed that rod-shaped SBA-15 materials displayed higher degradability when the concentration of H3PO4 was increased. An indirect cell viability assay with MC3T3-E1 osteoblast precursor cells was performed by incubating cells in cell culture medium exposed to SBA-15 particles for 1 and 4 days. The results obtained from the WST-8 assay and fluorescent staining showed no negative effect on cell viability, indicating a lack of cytotoxicity of the rod-like SBA-15 particles.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Bioactivity; Cytocompatibility; Degradability; Rod-like SBA-15 particles; Solvents extraction

Effect of Sr, Mg and Fe substitution on the physico-chemical and biological properties of Si[sbnd]Ca[sbnd]P multilayer scaffolds Efecto de la sustitución de Sr, Mg y Fe en las propiedades físico-químicas y biológicas de andamios multicapa de Si-Ca-P - Mata, Nayarit A.; Arango Ospina, Marcela; Velasquez, Pablo; Murciano, Angel; De Aza, Piedad N.; Boccaccini, Aldo R. (Boletin De La Sociedad Espanola De Ceramica Y Vidrio, 2021)
In this work, a new combination of ceramic materials is proposed for bone tissue engineering applications. Multilayer scaffolds consisting of a core composed mainly of calcium pyrophosphate and external coatings of silica and calcium doped with Fe3+, Sr2+ and Mg2+ were prepared. To study the influence of the arrangement of dopant ions in the external coatings, two different scaffolds were developed: scaffolds 3J consisting of a single external coating with 9 mol% of Fe3+, Sr2+ and Mg2+ ions; and scaffolds 3S comprising three external coatings, each containing 3 mol% of Fe3+, Sr2+ and Mg2+ ions. Scaffolds were physico-chemically characterized and evaluated for in vitro bioactivity and cellular response in the presence of MG-63 cells. The results showed that the core scaffold displayed no in vitro bioactivity or good cellular response, but served as a support for the external coatings given its mechanical resistance. The cell viability of scaffolds 3J and 3S increased more than 100% in relation to the core, and also improved cell proliferation and adhesion resulting in a dense layer of cells that covered the scaffolds’ entire surface. The arrangement of ions in the external coatings did not influence the cellular response, but determined the bioactivity rate.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Bioceramics; Ion doping; Scaffolds; Sol–gel

Facile preparative access to bioactive silicon oxycarbides with tunable porosity - Xie, Fangtong; Ionescu, Emanuel; Arango Ospina, Marcela; Riedel, Ralf; Boccaccini, Aldo R.; Gonzalo-Juan, Isabel (Materials, 2019)
In the present work, Ca-containing silicon oxycarbides (SiCaOC) with varying Ca content have been synthesized via sol-gel processing and thermal treatment in inert gas atmosphere (pyrolysis). It has been shown that the as-prepared SiCaOC materials with low Ca loadings (Ca/Si molar ratios = 0.05 or 0.12) were X-ray amorphous; their glassy network contains Q3 sites, indicating the presence of Ca2+ at non-bridging-oxygen sites. SiCaOC with high Ca content (i.e., Ca/Si molar ratio = 0.50) exhibits the presence of crystalline calcium silicate (mainly pseudowollastonite). Furthermore, it has been shown that the incorporation of Ca into the SiOC glassy network has a significant effect on its porosity and specific surface area. Thus, the as-prepared Ca-free SiOC material is shown to be non-porous and having a specific surface area (SSA) of 22.5 m2/g; whereas SiCaOC with Ca/Si molar ratio of 0.05 exhibits mesoporosity and a SSA value of 123.4 m2/g. The further increase of Ca content leads to a decrease of the SSA and the generation of macroporosity in SiCaOC; thus, SiCaOC with Ca/Si molar ratio of 0.12 is macroporous and exhibits a SSA value of 39.5 m2/g. Bioactivity assessment in simulated body fluid (SBF) confirms the hydroxyapatite formation on all SiCaOC samples after seven days soaking, unlike the relatively inert ternary silicon oxycarbide reference. In particular, SiCaOC with a Ca/Si molar ratio of 0.05 shows an increased apatite forming ability compared to that of SiCaOC with Ca/Si molar ratio of 0.12; this difference is considered to be a direct consequence of the significantly higher SSA of the sample with the Ca/Si ratio of 0.05. The present work indicates two effects of Ca incorporation into the silicon oxycarbide glassy network on its bioactivity: Firstly, Ca2+ is shown to contribute to the slight depolymerization of the network, which clearly triggers the hydroxyapatite formation (compare the bioactive behavior of SiOC to that of SiCaOC with Ca/Si molar ratio 0.12 upon SBF exposure); secondly, the Ca2+ incorporation seems to strongly affect the porosity and SSA in the prepared SiCaOC materials. There is an optimum of Ca loading into the silicon oxycarbide glassy network (at a Ca/Si molar ration of 0.05), which provides mesoporosity and reaches maximum SSA, both highly beneficial for the bioactive behavior of the materials. An increase of the Ca loading leads, in addition to the crystallization of calcium silicates, to a coarsening of the pores (i.e., macroporosity) and a significant decrease of the SSA, both negatively affecting the bioactivity.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Apatite forming ability; Bioactivity; Mesoporosity; Silicon oxycarbide; Sol-gel; Specific surface area

In vitro and in ovo impact of the ionic dissolution products of boron-doped bioactive silicate glasses on cell viability, osteogenesis and angiogenesis - Decker, Simon; Arango Ospina, Marcela; Rehder, Felix; Moghaddam, Arash; Simon, Rolf; Merle, Christian; Renkawitz, Tobias; Boccaccini, Aldo R.; Westhauser, Fabian (Scientific Reports, 2022)
Due to the pivotal role of angiogenesis in bone regeneration, the angiogenic properties of biomaterials are of high importance since they directly correlate with the biomaterials' osteogenic potential via 'angiogenic-osteogenic coupling' mechanisms. The impact of bioactive glasses (BGs) on vascularization can be tailored by incorporation of biologically active ions such as boron (B). Based on the ICIE16-BG composition (in mol%: 49.5 SiO2, 36.3 CaO, 6.6 Na2O, 1.1 P2O5, 6.6 K2O), three B-doped BGs have been developed (compositions in mol%: 46.5/45.5/41.5 SiO2, 36.3 CaO, 6.6 Na2O, 1.1 P2O5, 6.6 K2O, 3/4/8 B2O3). The influence of B-doping on the viability, cellular osteogenic differentiation and expression of osteogenic and angiogenic marker genes of bone marrow-derived mesenchymal stromal cells (BMSCs) was analyzed by cultivating BMSCs in presence of the BGs' ionic dissolution products (IDPs). Furthermore, the influence of the IDPs on angiogenesis was evaluated in ovo using a chorioallantoic membrane (CAM) assay. The influence of B-doped BGs on BMSC viability was dose-dependent, with higher B concentrations showing limited negative effects. B-doping led to a slight stimulation of osteogenesis and angiogenesis in vitro. In contrast to that, B-doping significantly enhanced vascularization in ovo, especially in higher concentrations. Differences between the results of the in vitro and in ovo part of this study might be explained via the different importance of vascularization in both settings. The implementation of new experimental models that cover the 'angiogenic-osteogenic coupling' mechanisms is highly relevant, for instance via extending the application of the CAM assay from solely angiogenic to angiogenic and osteogenic purposes.
CRIS-Team WoS Importer:2022-06-03

Manuka Honey and Zein Coatings Impart Bioactive Glass Bone Tissue Scaffolds Antibacterial Properties and Superior Mechanical Properties - Arango Ospina, Marcela; Lasch, Kristina; Weidinger, Julius; Boccaccini, Aldo R. (Frontiers in Materials, 2021)
The combination of traditional herbal medicine (phytotherapeutic agents) with bioactive glasses is a promising strategy to generate advanced scaffolds for bone tissue engineering (BTE). An old remedy used for wound care since ancient times is honey. The antioxidant, antimicrobial and antibacterial properties of Manuka honey, in particular, make it an attractive substance for application in BTE scaffolds to prevent infections and biofilm formation. In this study 45S5 bioactive glass-based scaffolds produced via the foam replica technique were coated with corn protein zein and Manuka honey with two purposes: to improve the mechanical properties of the brittle scaffolds and to impart antibacterial properties. The morphology and chemical composition of the coated scaffolds were characterized with scanning electron microscopy and Fourier transform infrared spectroscopy, respectively, demonstrating the presence of Manuka honey in the coating. The release of the honey was quantified via ultraviolet-visible spectrophotometry; moreover, the antibacterial activity against Staphylococcus aureus was evaluated via colony-forming units counting, reduction of Alamar blue and turbidity measurements. Our findings suggest the effective combination of Manuka honey and bioactive glass, adding one more system to the novel family of bioactive glass scaffolds functionalized with phytotherapeutic agents.
CRIS-Team WoS Importer:2021-03-05

Poly(Glycerol Succinate) as Coating Material for 1393 Bioactive Glass Porous Scaffolds for Tissue Engineering Applications - Nakiou, Eirini A.; Lazaridou, Maria; Pouroutzidou, Georgia K.; Michopoulou, Anna; Tsamesidis, Ioannis; Liverani, Liliana; Arango Ospina, Marcela; Beketova, Anastasia; Boccaccini, Aldo R.; Kontonasaki, Eleana; Bikiaris, Dimitrios N. (Polymers, 2022)
Background: Aliphatic polyesters are widely used for biomedical, pharmaceutical and environmental applications due to their high biodegradability and cost-effective production. Recently, star and hyperbranched polyesters based on glycerol and ω-carboxy fatty diacids have gained considerable interest. Succinic acid and bio-based diacids similar to glycerol are regarded as safe materials according to the US Food and Drug Administration (FDA). Bioactive glass scaffolds utilized in bone tissue engineering are relatively brittle materials. However, their mechanical properties can be improved by using polymer coatings that can further control their degradation rate, tailor their biocompatibility and enhance their performance. The purpose of this study is to explore a new biopolyester poly(glycerol succinate) (PGSuc) reinforced with mesoporous bioactive nanoparticles (MSNs) as a novel coating material to produce hybrid scaffolds for bone tissue engineering. Methods: Bioactive glass scaffolds were coated with neat PGSuc, PGSuc loaded with dexamethasone sodium phosphate (DexSP) and PGSuc loaded with DexSP-laden MSNs. The physicochemical, mechanical and biological properties of the scaffolds were also evaluated. Results: Preliminary data are provided showing that polymer coatings with and without MSNs improved the physicochemical properties of the 1393 bioactive glass scaffolds and increased the ALP activity and alizarin red staining, suggesting osteogenic differentiation potential when cultured with adipose-derived mesenchymal stem cells. Conclusions: PGSuc with incorporated MSNs coated onto 1393 bioactive glass scaffolds could be promising candidates in bone tissue engineering applications.
CRIS-Team Scopus Importer:2022-12-02
Keywords: 1393 bioactive glass scaffolds; bioactivity; dexamethasone; glycerol; mechanical properties; mesoporous nanoparticles; osteogenic differentiation; succinic acid

Preconditioning of bioactive glasses before introduction to static cell culture: What is really necessary? - Hohenbild, Frederike; Arango Ospina, Marcela; Moghaddam, Arash; Boccaccini, Aldo R.; Westhauser, Fabian (Methods and Protocols, 2020)
Due to their high bioreactivity, the in-vitro analysis of bioactive glasses (BGs) can be challenging when it comes to maintaining a physiological pH. To improve BG biocompatibility, a heterogenic spectrum of preconditioning approaches, such as “passivation” of the BGs by incubation in cell culture medium, are used but have never been directly compared. In this study, the effect of passivation periods of up to 72 h on pH alkalization and viability of human bone marrow-derived mesenchymal stromal cells was evaluated to determine a time-efficient passivation protocol using granules based on the 45S5-BG composition (in wt%: 45.0 SiO2, 24.5 Na2 O, 24.5 CaO, 6.0 P2 O5) in different concentrations. pH alkalization was most reduced after passivation of 24 h. Cell viability continuously improved with increasing passivation time being significantly higher after passivation of at least 24 h compared to non-passivated 45S5-BG and the necessary passivation time increased with increasing BG concentrations. In this setting, a passivation period of 24 h presented as an effective approach to provide a biocompatible cell culture setting. In conclusion, before introduction of BGs in cell culture, different passivation periods should be evaluated in order to meet the respective experimental settings, e.g., by following the experimental protocols used in this study.
CRIS-Team Scopus Importer:2020-09-04
Keywords: 45S5 bioactive glass; Biocompatibility; Cytocompatibility; Cytotoxicity; Human bone marrow-derived mesenchymal stromal cells; Passivation

PVA-gelatine based hydrogel loaded with astaxanthin and mesoporous bioactive glass nanoparticles for wound healing - Hernandez Rivera, Gabriela; Valdez, Hugo A.; Arango Ospina, Marcela; Delgado, Juan Francisco; Aguilar-Rabiela, Arturo E.; Gorgojo, Juan Pablo; Zhang, Huijun; Beltrán, Ana M.; Boccaccini, Aldo R.; Sanchez, Mirna (Journal of Drug Delivery Science and Technology, 2024)
Astaxanthin (AST) is a potent antioxidant phytochemical used in wound healing with promising results in-vitro. However, AST incorporation into clinical practice still faces challenges related to the susceptibility of AST to instability. One of the most innovative solutions proposed is the encapsulation of AST into hydrogels. This study focuses on innovating the wound healing potential of AST-containing hydrogels by introducing silicate mesoporous bioactive glass nanoparticles (MBGNs). These nanoparticles release biologically active ions that accelerate cell proliferation and migration. The results showcase an innovative synergistic effect between 1 μg/mL of AST with 100 μg/mL of MBGNs, outperforming the individual proliferation effect of AST or MBGNs alone. Separately, these compounds were encapsulated in physical and chemical cross-linked hydrogel for the compound protection and delivery, finding that PVA-gelatine hydrogels are a suitable matrix for the delivery of AST and MBGNs. Physically crosslinked hydrogels showed particularly convenient characteristics for potential clinical implementation while maintaining the synergetic effect of AST and MBGNs. Although chemically crosslinked hydrogels exhibited suitable characteristics as a vehicle for AST in biological assays, cell proliferation was reduced by 57 %. The results of this research open avenues for exploring the development of new composite matrices for the co-delivery of phytochemicals and MBGNs for cutting-edge biomedical applications.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Astaxanthin; Bioactive glass; Hydrogels; Wound healing

Review: Silicon oxycarbide based materials for biomedical applications - Arango Ospina, Marcela; Xie, Fangtong; Gonzalo-Juan, Isabel; Riedel, Ralf; Ionescu, Emanuel; Boccaccini, Aldo R. (Applied Materials Today, 2019)
Silicon oxycarbide (SiOC) based materials are of interest due to their unique properties, including high-temperature resistance, mechanical strength, chemical durability and corrosion resistance. The versatility of the silicon oxycarbide chemistry allows the modification of properties for different fields. In the last decade, attention has been paid to the potential use of SiOC materials in biomedical applications. Surface functionalization of SiOC is a promising approach to create efficient and controllable drug delivery systems with adequate molecule adsorption and release kinetics. The analysis of the literature reveals that silicon oxycarbides have also potential applications as protective biocompatible coatings, for example in blood-contact devices. Additionally, by incorporating metallic ions (i.e. Ca2+, Mg2+, Ag+) in the material network structure, promising antibacterial properties and bioactive behavior have been observed despite the high network connectivity values compared to silicate bioactive glasses. This review covers studies which have reported the use of silicon oxycarbide based materials for biomedical applications. Advances in the evaluation of biocompatibility, bioactivity, surface functionalization and antibacterial effects are discussed in detail, highlighting advantages and limitations of SiOC systems in the biomedical field.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Bioactive glass; Biocompatibility; Coating; Cytotoxicity; Polymer-derived ceramic; Silicon oxycarbide

Selective and caspase-independent cytotoxicity of bioactive glasses towards giant cell tumor of bone derived neoplastic stromal cells but not to bone marrow derived stromal cells. - Westhauser, Fabian; Arango Ospina, Marcela; Losch, Sarina; Wilkesmann, Sebastian; Lehner, Burkhard; Ali, Muhammad Saad; Peukert, Wolfgang; Boccaccini, Aldo R.; Fellenberg, Jörg (Biomaterials, 2021)
Semi-malignant giant cell tumors of bone (GCTB) are associated with large osteolytic defects and significant bone destructions. Surgical resection remains the standard therapy that is, however, associated with very high recurrence rates. Bioactive glasses (BGs) that are osteogenic but under certain conditions also cytotoxic might be suitable to achieve biological reconstruction with simultaneous reduction of tumor recurrence in GCTB. In this study, a concentration and time dependent cytotoxic effect of five different BG compositions towards neoplastic GCTB cells was identified while bone marrow derived mesenchymal stromal cells were mostly unaffected. Time course and extent of the cytotoxic effect were dependent on the BG composition and were not associated with caspases activation, indicating that apoptotic mechanisms are not involved. Rather, detection of BG-induced disruption of the cell membranes and a rapid drop of intracellular HMG1 (High Mobility Group Box 1 protein) levels suggest a necrotic cell death. Notably, the cytotoxic effects were dependent on a direct contact of cells and BGs and could not be observed using indirect cultivation settings. Our data suggest that BGs might represent promising materials for the treatment of GCTB in order to reduce tumor recurrence with simultaneous enhancement of bone regeneration.
Keywords: Apoptosis; Bioactive glass; Caspases; Cytotoxicity; Giant cell tumor of bone; Mesenchymal stromal cells; Necrosis

Silicate-based nanoceramics in regenerative medicine - Arango Ospina, Marcela; Nawaz, Qaisar; Boccaccini, Aldo R. (Nanostructured Biomaterials for Regenerative Medicine, 2020)
Silicate-based bioactive nanoceramics, such as bioactive glasses, glass-ceramics, and mesoporous systems play an important role in biomedical applications, tissue engineering, bioimaging, and drug delivery systems. The structure and chemistry of these inorganic materials can be tailored to achieve controlled degradation rate that mimics the new tissue growth rate. Furthermore, these materials are combined with different polymeric systems to form nanocomposites with enhanced mechanical properties and improved biological performance. This chapter provides an overview of the processing and application of different silicate-based nanoceramics and bioactive glasses. It also addresses the interaction of silicate-based systems with the biological environment, giving a brief overview on the applications of bioactive silicate nanoparticles in bone regeneration, soft tissue repair, and as targeted drug delivery carriers.<br
CRIS-Team WoS Importer:2020-05-26
Keywords: Silicate-based nanoceramics; Silicate-based bioactive glasses; Tissue engineering; Mesoporous systems; Drug delivery

Sol–gel synthesis and characterization of ysz nanofillers for dental cements at different temperatures - Beketova, Anastasia; Theocharidou, Anna; Tsamesidis, Ioannis; Rigos, Athanasios E.; Pouroutzidou, Georgia K.; Tzanakakis, Emmanouil George C.; Kourtidou, Dimitra; Liverani, Liliana; Arango Ospina, Marcela; Anastasiou, Antonios; Tzoutzas, Ioannis G.; Kontonasaki, Eleana (Dentistry Journal, 2021)
Background: Yttria-stabilized zirconia nanoparticles can be applied as fillers to improve the mechanical and antibacterial properties of luting cement. The aim of this study was to synthesize yttria-stabilized zirconia nanoparticles by the sol–gel method and to investigate their composition, structure, morphology and biological properties. Methods: Nanopowders of ZrO2 7 wt% Y2O3 (nY-ZrO) were synthesized by the sol–gel method and were sintered at three different tempera-tures: 800, 1000 and 1200◦C, and their composition, size and morphology were investigated. The biocompatibility was investigated with human gingival fibroblasts (hGFs), while reactive oxygen species (ROS) production was evaluated through fluorescence analysis. Results: All synthesized materials were composed of tetragonal zirconia, while nanopowders sintered at 800◦C and 1000◦C additionally contained 5 and 20 wt% of the cubic phase. By increasing the calcination temperature, the crystalline size of the nanoparticles increased from 12.1 nm for nY-ZrO800 to 47.2 nm for nY-ZrO1200. Nano-sized particles with good dispersion and low agglomeration were received. Cell culture studies with human gingival fibroblasts verified the nanopowders’ biocompatibility and their ROS scavenging activity. Conclusions: the obtained sol–gel derived nanopowders showed suitable properties to be potentially used as nanofillers for dental luting cement.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Chemical precipitation; Gingival fibroblasts; Nanoparticle; Oxidative stress; Toxicity tests; Yttrium; Zirconium

Study of the synergistic effects of bioactive glasses with Manuka honey - Lippert, Jessica; Arango Ospina, Marcela; Boccaccini, Aldo R. (Open Ceramics, 2025)
Bioactive glasses (BGs) are highly researched biomaterials in the field of bone tissue engineering. Besides their good biocompatibility and biodegradability, they also develop osteogenic and angiogenic effects due to the release of several biologically active ions through the dissolution process. To further improve the functionality of BGs, different biomolecules can be added, which are then released into the body together with the BG ionic dissolution products. For this purpose, phytotherapeutic agents can be used, which have the potential advantage of inducing less undesirable side effects than synthetic drugs and can exhibit anti-inflammatory and antibacterial activity. A well-known example of such natural compounds is the Manuka honey from New Zealand, which was used in this project. The aim of this study was thus to investigate the synergistic effects of the dissolution products of bioactive glasses in combination with Manuka honey (MH). Different relevant bioactive glass compositions (45S5 BG, 13–93 BG and 0106-B1 BG) were combined with MH. Cell biology (osteoblast-like cell line MG-63) and antibacterial assays (E. coli and S. aureus) were performed. The results indicated synergistic effects of BGs and MH, particularly in relation to the antibacterial activity of BG-MH combinations, which resulted in overall bacteria viabilities of < 40% compared to 80% of viable bacteria for BG samples without MH. Interestingly, the ionic dissolution products from 13-93 BG and 0106-B1 BG showed superior effects on MG-63 cells when combined with MH compared with 45S5 BG at the same concentrations. These findings suggest that combining BGs with MH enhances the stimulatory effects on cells and bacteria, supporting the potential use of BGs in combination with natural compounds for tissue engineering applications.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Antibacterial effect; Bioactive glasses; Herbal medicine; Ionic medicine; Manuka honey; Phytotherapeutics

The Addition of Zinc to the ICIE16-Bioactive Glass Composition Enhances Osteogenic Differentiation and Matrix Formation of Human Bone Marrow-Derived Mesenchymal Stromal Cells - Rehder, Felix; Arango Ospina, Marcela; Decker, Simon; Saur, Merve; Kunisch, Elke; Moghaddam, Arash; Renkawitz, Tobias; Boccaccini, Aldo R.; Westhauser, Fabian (Biomimetics, 2024)
An ICIE16-bioactive glass (BG) composition (in mol%: 49.5 SiO2, 6.6 Na2O, 36.3 CaO, 1.1 P2O5, and 6.6 K2O) has demonstrated excellent in vitro cytocompatibility when cultured with human bone marrow-derived mesenchymal stromal cells (BMSCs). However, its impact on the development of an osseous extracellular matrix (ECM) is limited. Since zinc (Zn) is known to enhance ECM formation and maturation, two ICIE16-BG-based Zn-supplemented BG compositions, namely 1.5 Zn-BG and 3Zn-BG (in mol%: 49.5 SiO2, 6.6 Na2O, 34.8/33.3 CaO, 1.1 P2O5, 6.6 K2O, and 1.5/3.0 ZnO) were developed, and their influence on BMSC viability, osteogenic differentiation, and ECM formation was assessed. Compared to ICIE16-BG, the Zn-doped BGs showed improved cytocompatibility and significantly enhanced osteogenic differentiation. The expression level of the osteopontin gene was significantly higher in the presence of Zn-doped BGs. A larger increase in collagen production was observed when the BMSCs were exposed to the Zn-doped BGs compared to that of the ICIE16-BG. The calcification of the ECM was increased by all the BG compositions; however, calcification was significantly enhanced by the Zn-doped BGs in the early stages of cultivation. Zn constitutes an attractive addition to ICIE16-BG, since it improves its ability to build and calcify an ECM. Future studies should assess whether these positive properties remain in an in vivo environment.
CRIS-Team Scopus Importer:2024-02-02
Keywords: bone tissue engineering; human mesenchymal stromal cells; ICIE16-bioactive glass; osteogenic differentiation; zinc

Zinc and gallium doped borate bioactive glasses influence in-vitro angiogenesis: New evidence in cell co-culture studies - Mutlu, Nurshen; Arango Ospina, Marcela; Detsch, Rainer; Galusek, Dušan; Boccaccini, Aldo R. (Materials Letters, 2024)
Borate bioactive glasses doped with 1 mol% ZnO or Ga2O3 were produced by melt-quenching. The cytocompatibility of fibroblast and endothelial cells in response to glass extracts was assessed. The angiogenic potential was examined through fibroblast-derived vascular endothelial growth factor secretion and tubular formation analysis in an indirect co-culture of fibroblast and endothelial cells. The results confirm that Zn and Ga ion-releasing bioactive glasses are attractive biomaterials with angiogenic properties.
CRIS-Team Scopus Importer:2024-11-15